Efficacy of Intravitreal Injection of Filtered Modified Low-Dose Triamcinolone Acetonide and Ranibizumab on Pseudophakic Cystoid Macular Edema - Tariq, Farheen; Wang, Yanfen; Ma, Bo; He, Yidan; Zhang, Shu; Bai, Ling (Frontiers in Medicine, 2022)
Purpose To compare the visual and morphological effects between intravitreal injection of filtered modified 2 mg triamcinolone acetonide (TA) and 0. 5 mg ranibizumab in patients with pseudophakic cystoid macular edema (PCME). Methods A retrospective, interventional study was conducted from January 2015 to February 2020 involving patients with PCME after uneventful cataract surgery. A total of 25 patients (25 eyes) with PCME received an intravitreal injection of 0.22 μm filtered modified 2 mg TA, while 15 patients (15 eyes) received 0.5 mg ranibizumab injection. Central macular thickness (CMT), best-corrected visual acuity (BCVA), intraocular pressure (IOP), times of repeated injections, and other side effects were observed at 2 weeks, 1 month, 3 months, and 6 months after injection; then, the data were compared with preinjection information in each group and between the two groups. Results Both the TA and ranibizumab intravitreal injection can achieve improved BCVA and reduced CMT in patients with PCME (P < 0.05), with a trend toward greater improvement in the TA group, but the difference was only significant at 3 months (P < 0.05). IOP was in the normal range without any significant difference (P > 0.05). Thirty-three percent of patients in the ranibizumab group required repeated intravitreal injection compared to 4% in the TA group. Further stratified analysis showed that the better therapeutic effect of the TA group at 3 months after injection only existed in patients with diabetes mellitus (DM), while not in patients without DM. There was no repeat injection in the TA group and 12.5% in the ranibizumab group for patients without DM, while 16.7% in the TA group and 57.1% in the ranibizumab group required repeated injection for patients with DM, which had a significant difference (P < 0.05). Conclusion Intravitreal injection of filtered modified 2 mg TA is safe, effective, and an inexpensive alternative to antivascular endothelial growth factor (anti-VEGF) agents for patients with PCME, especially for patients concurrently with DM. A large number of clinical randomized controlled studies along with long-term follow-up observations are needed.